EKSPLORASI ETNOMATEMATIKA KONSEP BANGUN RUANG PADA KUE TRADISIONAL LAMPUNG - Pika Merliza; Henry Kurniawan; Uke Ralmugiz (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Mathematics is still considered difficult by some Indonesian students. This is because mathematics is still considered meaningless and culture-free. Indonesia is a rich country in term of culture. Various cultural objects can be integrated in the mathematics learning process. Therefore, the purpose of this study is to explore mathematical concepts that are integrated in cultural elements, traditional cakes from Lampung, Indonesia. This research was a qualitative descriptive study with an ethnographic approach. Data collection techniques were by observation, interviews, documentation and literature study. The results of this study indicated that traditional Lampung cakes such as selimpok, engkak, sekubal, bebai maghing, and buak tat contain mathematical concepts of 3D-Shape such as quadrilateral pyramids, cylinder, polygons, cubes and cuboids both in form and how to make them. The concept of volume has actually been applied since preparing the cake ingredients to the making process. This involves the concept of traditional estimation using “irus” (vegetable spoon) or glass and “rantang” (bowl) in estimating the number of ingredients that will be used as cake dough. Thus, this cultural object in the form of traditional Lampung cakes can be used as a source of learning both in terms of form and which making process can facilitate students in understanding mathematical concepts. It is hoped that cultural objects in the form of traditional Lampung cakes can be used as learning resources to facilitate mathematics learning